A highly selective colorimetric and fluorescent probe for cysteine sensing: Application in live cell imaging and test strips. (December 2021) - Chen, Xiaoxia; Huang, Xiaoqin; Liu, Gang; Tu, Yayi; Fan, Congbin; Pu, Shouzhi
Abstract: Here, a coumarin-based probe 4-chloro-3-formyl-2-oxo-2H-chromen-7-yl acrylate (named CFCA ), which performed high efficient and specific recognition for cysteine (Cys), was successfully synthesized and characterized by NMR and MS. The CFCA probe showed colorimetric and "turn-on" fluorescent signals to Cys, and its color changes could be recognized by naked eyes. CFCA responded to Cys with the characteristics of rapid response time (less than 40 s), high selectivity, and excellent anti-interference. Among all kinds of samples, only Cys could significantly enhance the fluorescence intensity of the solution, which was not affected by the presence of other interferences. At the same time, within a certain concentration range, there was a good linear relationship between relative intensity of fluorescence and Cys concentration. The detection limit has been calculated to be as low as 0.33 μM. And the sensing mechanism of CFCA with Cys has been well confirmed by 1 H NMR and HR-MS spectra. Moreover, the fluorescence probe CFCA was successfully used for imaging Cys in living cells and processed into test strips for on-site analysis and testing. Highlights: A coumarin-based probe CFCA was successfully prepared, synthesized, and applied for Cys detection. CFCA can perform high efficiency and specificity colorimetric and fluorescent double signal recognition for Cys. CFCA has been used for imaging Cys in living cells and processed into test strips for on-site analysis and testing.